Turkish EFL learners’ perceptions of using ChatGPT vs. online dictionaries for English collocations - Berra Artul (Journal of Language, Literature, Social and Cultural Studies, 2026)
This study investigates Turkish EFL (English as a Foreign Language) learners’ perceptions, attitudes, and usage patterns regarding ChatGPT and online dictionaries for the acquisition of English collocations. Utilizing a quantitative research design, data were collected via an online questionnaire from 27 university-level participants, including preparatory and master’s students. The findings reveal that while online dictionaries remain the primary and most trusted resource for checking grammatical patterns and seeking reliable definitions (M=3.81), ChatGPT is increasingly perceived as a valuable "language assistant" for production-based tasks. Specifically, participants rated online dictionaries higher for reliability and ease of use. However, ChatGPT was perceived as more effective for improving writing (M=4.11) and speaking (M=4.04) skills due to its ability to provide personalized feedback and generate contextualized examples. Despite the benefits of AI (Artificial Intelligence), learners demonstrated a cautious approach, often using ChatGPT as a "gap-filler" rather than a primary source. The study concludes that the integration of AI tools does not replace traditional resources but rather offers a complementary framework where dictionaries serve verification purposes and AI facilitates linguistic exploration. Pedagogical implications suggest that educators should provide explicit training on leveraging both tools to foster autonomous and context-aware collocation learning.